Oxidative coupling of ortho - aminophenol over mesoporous silica containing copper (11) diethylamino -substituted salen complex - Chin, Tian Kae, 1983-; Salasiah Endud; Shajarajtunnur Jamil, supervisor; Fakulti Sains (2010)
Thesis (Sarjana Sains (Kimia)) - Universiti Teknologi Malaysia, 2010